The Clinical Importance of Optic Nerve Sheath Diameter in Patients with Traumatic Brain Injury: Preliminary Report - Burcu AVCI OZBALIK; Tugba BINGOL TANRIVERDI; Hafize Gulsah OZCAN; Melek GURA CELIK (Medeniyet Medical Journal)
Objective: Traumatic brain injury (TBI) is a serious health problem that is related to an increased mortality. In cases of severe TBI, the prediction of prognosis is essential. The enlargement of the optic nerve sheath diameter (ONSD) shows an increased intracranial pressure and is associated with poor outcomes. In this study, we aimed to evaluate the prognostic value of ONSD in patients with severe TBI. Methods: Forty-four patients with severe TBI were retrospectively enrolled in the study. The patients were divided into two groups: survivors (n=17) and non-survivors (n=27). Baseline characteristics, clinical data, Glasgow coma scale (GCS) on hospital admission, brain computed tomography (CT) results, injury severity score (ISS), and Marshall score were recorded for all patients. ONSD was calculated at 3 mm distance from the globe, immediately below the sclera. Results: The ONSD on the initial CT was significantly higher in non-survivors compared with survivors (6.83+-1.40 vs. 6.40+-1.36, p<0.05). In addition, ISS and Marshall score were significantly higher, whereas GCS was significantly lower in non-survivors. ONSD was positively correlated with Marshall score (r=0.332, p<0.05). Receiver operating characteristics analysis demonstrated that ONSD ≥6.61 had a sensitivity of 70.4% and specificity of 64.7% for predicting mortality. It was shown that ONSD ≥6.61 had a 4.3-fold increased risk for in-hospital mortality (odds ratio: 4.35; 95% confidence interval: 1.195-15.865; p<0.05). Conclusions: The enlargement of ONSD on initial CT was detected to be associated with increased in-hospital mortality in patients with severe TBI.